Circumosseous wire fixation for metacarpal fractures: an old method revisited - Malik, Anil; Malik, Parvesh; Pandey, Vijay Kumar; Sharma, Dev Jyoti; Pushkar, Kumar (International Surgery Journal, 2020)
Background: Different methods are in use for fixation of metacarpal fractures. Krischener wire and titanium miniplates are most commonly used methods. Both these methods require special & sophisticated instruments. In this study, we have used a dental wire in circumosseous fashion to fix the metacarpal fractures. Methods: In the study, we included all the fracture of metacarpals with operative indication. K-wire, minilplate system and circumosseous dental wire methods were used randomly. Results: The results were compared in term of immediate post-operative complications & functional recovery in form of ability of fist formation at 06 weeks. All the three methods were found comparable, in fact in this study the results of fractures treated with circumosseous wiring were appreciable and significantly better. Conclusions: Circumossoeus use of dental wire can be an alternate method of metacarpal fracture fixation.